Powder milk: a user-friendly and safe product for heated-milk food challenge?. Issue 1 (December 2015) - Cherkaoui, Sabrine; Bégin, Philippe; Paradis, Louis; Paradis, Jean; Roches, Anne
Abstract Background Previous studies have reported that up to 75 % of milk allergic subjects tolerate heated milk products. However, the food used for heated milk challenge is often prepared in a non-standardized manner by the parents at home, which may prove inconvenient and even sometimes raise concerns with regards to test validity. Instant skim milk powder is made by a food process that involves heating skim milk to up to 250 °C (390 °F) for up to 30 min which ought to be sufficient to denature thermo-labile proteins. Objective To appraise the use of instant skim milk for the purpose of heated milk food challenge. Methods We reviewed all oral food challenges to instant skim milk powder performed at Sainte-Justine University Hospital Center in Montreal, Canada between November 2008 and January 2013 (cumulative dose of 4 g proteins). Results During the study period, 39 children underwent an open food challenge to instant skim milk powder. Thirty patients (76.9 %) passed the challenge without clinical reaction, of which 26 successfully introduced heated milk products at home. The remaining four children reported intermittent mild reactions to specific forms of heated milk goods while they tolerated others. Subjects' clinical and paraclinical characteristics were comparable to previous cohorts evaluating baked milk challenge, which reported similar rates of heated milk positive challenges, ranging from 17 to 28 %. Conclusion Challenge with instant skim milk powder could be a safe, convenient and easily standardizable alternative to home baked food for heated milk challenge. Further controlled studies are needed before this can be implemented to practice.